2010
DOI: 10.1007/s00464-010-1513-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of suprapubic hernias: transabdominal partial extraperitoneal (TAPE) technique

Abstract: A mesh overlap of at least 5 cm and fixation of the lower margin of the mesh under direct vision to Cooper's ligaments appears to confer increased strength and durability and contribute to low hernia recurrence rates in patients with suprapubic hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 16 publications
1
39
0
2
Order By: Relevance
“…The concept of laparoscopic trans-abdominal partial extra-peritoneal (TAPE) technique was further consolidated by Sharma et al and published in 2011. 8 With this hybrid approach, part of the prosthetic mesh is being placed intra-peritoneally to cover the defect, where the inferior part is being placed at pre-peritoneal space and covered up by the peritoneal flap after completion of procedure (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of laparoscopic trans-abdominal partial extra-peritoneal (TAPE) technique was further consolidated by Sharma et al and published in 2011. 8 With this hybrid approach, part of the prosthetic mesh is being placed intra-peritoneally to cover the defect, where the inferior part is being placed at pre-peritoneal space and covered up by the peritoneal flap after completion of procedure (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report in 2001 [176], experience with laparoscopic treatment of such hernias is limited and longterm follow-up between 2.6 months [177] and 4.8 years [178] in the four largest series. Authors agree that laparoscopy allows complete assessment of both the hernia defect and prior scar with reduced chance of ''missed'' defects [177,178].…”
Section: Suprapubic Incisional Herniasmentioning
confidence: 97%
“…No comparative studies with the open technique were found, and only one article was published on this specific topic since 2009; this retrospective study of 72 patients over a period of 10 years is the largest series of laparoscopic repair of suprapubic hernias to date [179]. All the authors underline the importance of preperitoneal surgical dissection by developing a peritoneal flap with direct visualization of the pubic bone, Cooper's ligaments, and the inferior epigastric and iliac vessels to obtain sufficient mesh overlap in an area with limited space [177][178][179][180]. Most of the authors advocate the elevation of the peritoneum flap with the bladder at the end of the procedure to cover Cooper's ligaments and the inferior mesh edge, repositioning the bladder to its normal anatomic position [176][177][178][179].…”
Section: Suprapubic Incisional Herniasmentioning
confidence: 97%
See 2 more Smart Citations